Forgotten urological stent. - Bhuiyan, ZH; Bhuiyan, NI; Khan, SA; Tawhid, MH; Islam, MF (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2011 Oct;20(4):632-9 The abstract of this article is available on the PubMed website